ANALYSIS OF THE SPRINGATE METHOD TO PREDICT BANKRUPTCY IN PT. AIR ASIA INDONESIA TBK PERIOD 2018-2022: ANALISIS METODE SPRINGATE UNTUK MEMPREDIKSI KEBANGKRUTAN DI PT. AIR ASIA INDONESIA TBK PERIODE 2018-2022 - Rizha Rizha; Edi Yanto (International Journal of Economic Entrepreneurship and Business Management, 2024)
The purpose of this study is to analyze the prediction of bankruptcy in PT. Air Asia Indonesia Tbk by using the Springate Method (S-score) for the 2018-2022 Period. This research was conducted on PT. Air Asia Indonesia Tbk. Using data sources accessed through the official website (www.idx.co.id). The type of data is secondary data, and the type of research is in the form of quantitative research with data collection techniques in the form of documentation and literature studies. The results of PT. Air Asia Indonesia Tbk. in 2018 obtained a Sscore value of -0.62918 so that it is categorized as experiencing financial distress or potentially experiencing bankruptcy. In 2019, PT. Air Asia Indonesia Tbk. obtained an S-Score of 0.43773 so it is categorized as experiencing financial distress or potentially experiencing bankruptcy. In 2020, PT. Air Asia Indonesia Tbk. obtained an S-Score of -2.79858 so it is categorized as experiencing financial distress or potentially experiencing bankruptcy. In 2020, PT. Air Asia Indonesia Tbk. obtained an S-Score of -2.50815 so it is categorized as experiencing financial distress or potentially experiencing bankruptcy. And in 2022 also PT. Air Asia Indonesia Tbk. obtained an S-Score of -1.99309 so it is categorized as experiencing financial distress or potentially experiencing bankruptcy